Application of Vector Sensors to Acoustic Surveillance of a Public Interior Space - ŁOPATKA, Kuba; KOTUS, Józef; CZYŻEWSKI, Andrzej (Archives of Acoustics, 2011)
A method for precise sound sources detection and localization in interiors ispresented. Acoustic vector sensors, which provide multichannel output signals ofacoustic pressure and particle velocity were employed. Methods for detecting acous-tic events are introduced. The algorithm for localizing sound events in the audienceis presented. The system set up in a lecture hall, which serves as a demonstratorof the proposed technology, is described. The accurracy of the proposed method isevaluated by the described measurement results. The analysis of the results is fol-lowed by conclusions pertaining the usability of the proposed system. The concept ofthe multimodal audio-visual detection of events in the audience is also introduced.